Control of virtual power plant in microgrids: a coordinated approach based on photovoltaic systems and controllable loads - Liu, Yun; Xin, Huanhai; Wang, Zhen; Gan, Deqiang (IET generation, transmission & distribution, 2015)
Renewable energy sources (RESs) such as solar energy are cost-effective to meet part of the energy needs. However, the inherent fluctuation and intermittence of RESs may deteriorate the stability and security of power grids. Energy storage systems can mitigate the problem, but they are very expensive. For this reason, a coordinated control method of virtual power plant (VPP), which includes photovoltaic systems (PVs) and controllable loads, is proposed in this study so that the aggregated power output of the VPP can be flexibly adjusted in a wide range. To achieve this, power output of the PVs and operational modes of controllable loads are coordinated by solving a mixed integer programming (MIP) problem. Meanwhile, with a quadratic interpolation based active power control strategy, each PV can operate in a power dispatch mode and simultaneously estimate its maximum available power, which is an input to the MIP problem. Externally, the VPP can quickly adjust the aggregated power and achieve functions important to power systems with high penetration of distributed energy resources, such as primary frequency regulation. Simulation results validate the effectiveness of VPP in providing frequency support to an island microgrid.